Mencerahkan Rohani Purnawirawan Polri Melalui Peningkatan Pemahaman Agama - Dahlan R, M (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2025)
Increasing religious understanding as an effort to enlighten the spirituality of retired National Police officers. Retired National Police officers face unique challenges in the post-service transition, which often includes changes in roles, social environment, and psychological conditions. A deep understanding of religion provides a strong foundation for building spiritual resilience, giving meaning to life, and guiding individuals in navigating a new phase of life with calmness and optimism. This service at the Darussalam mosque, located within the National Police complex, was attended by 80 participants. It featured Hadith material with the theme of many paths to goodness, a period of three months with an interactive, integral approach. The results show that there is an increase in religious knowledge, accompanied by an understanding of the basics in carrying out goodness, and knowledge about various ways to do good beyond the usual mahdhoh worship. The results of this service can contribute to the development of relevant and sustainable spiritual coaching programs for retired Police officers, enabling them to continue playing an active role in society with enhanced spiritual qualities.